Structure of starch, focusing on those from underground plant organs - Moretti, Marcia Maria de Souza [UNESP]; Costa, Mariana Souza; Bai, Yeming; Gilbert, Robert G.; Rocha, Thais de Souza (Elsevier, 2022)
This chapter provides information regarding the morphological, crystalline, and molecular structures of starches from underground plant organs in the light of recent technologies and methodologies, to bring an understanding of the relationship between the functional properties and structural characteristics. These starches come from three storage organs: roots, tubers, and rhyzomes. Some starches showed distinct thermal properties due to the biosynthesis packaging of starch molecules and the presence of minor constituents that impact structural and functional properties. Information about the starch structure of cereals and pulses is also applicable to starches from underground organs; three better-known ones, potato, cassava, and sweet potato, are discussed here. This chapter also points the way to further research into the structure of unconventional starches from underground starchy plants organs, using the techniques cited to investigate possible subtle structural differences that may affect their technological properties.
Keywords: amylose; biosynthesis; crystallinity; Hierarchical organization levels; methods; rhizomes; roots; tubers